How illegal capture of Glass Eel (Anguilla anguilla) affect biodiversity in tagus river - Garcia, Jorge (2014)
The eel is a catadromous fish that grows in rivers and spawns in the sea. Every year, between November and the end of March, when glass eels migrate up river, illegal nets catch them in the Tagus River (downstream of the estuary, in Portugal). Every day, authorities organise policing actions to capture illegal nets placed in river specifically intended to capture glass eels. Usually, the seized nets are filled with glass eels and other species, since the net is very narrow (1-2 mm); it therefore captures everything. The mortality rate caused by these is huge and affects the eel’s preservation and the river’s biodiversity.